The unfading power of collegiality? University governance in Poland in a European comparative and quantitative perspective - Kwiek, Marek (My University, 2015)
This paper studies the applicability of theoretical models of university governance from the international research literature to the Polish system. In particular, it is to test the applicability of a collegial model in the Polish case. The research question was ‘to what extent is a collegial model reflected in actual governance patterns found in the Polish university sector’. This is based on large-scale internationally comparable quantitative material. The empirical evidence for it comes from 3700 returned surveys in Poland (and more than 17,000 in eleven European countries) produced for two international research projects focused on the academic profession (CAP: “Changing Academic Profession” and EUROAC: “The Academic Profession in Europe”). This paper concludes that Polish universities are operating according to the traditional collegial model of the university as a “community of scholars” to an extent that is unparalleled in Western Europe. A detailed study of selected variables and specifically constructed indexes indicates that the defining feature of Polish academia today is the power of academic collegial bodies. The influence of collegial bodies on academic decision-making in Poland is the highest in Europe; and, in contrast, the power of the government and external stakeholders is the lowest. However, academics, sharing the “republic of scholars” institutional vision of the university, and still highly influential in university decision-making, are currently confronted with higher education reforms grounded in an instrumental vision of the university (in which it is a tool for national political agendas). Consequently, powerful value-driven clashes between the academic community and the community of policymakers and reformers are to be expected to intensify. The major theoretical concepts used in this paper come from Johan P. Olsen’s, Ian McNay’s and Robert Birnbaum’s studies of university governance, and its findings are presented from a European comparative and quantitative perspective.
Keywords: Polish higher education; Polish universities; Polish academic profession; European academic profession; academic collegiality; collegial bodies; CAP survey; EUROAC; CAP dataset; republic of scholars; academic entrepreneurialism; Johan P. Olsen; institutionalism; institutional and instrumental; university governance; governance models; university visions; Polish academics; European academics; comparative approach; quantitative; higher education research; junior-senior; index of collegiality; index of entrepreneurialism; Poland; higher education reforms; university reforms; governance reforms; Polish reforms; community of scholars; professorially-coordinated